Incidence, timing, predictors and impact of acute heart failure complicating ST-segment elevation myocardial infarction in patients treated by primary percutaneous coronary intervention. (15th October 2016) - Auffret, Vincent; Leurent, Guillaume; Gilard, Martine; Hacot, Jean-Philippe; Filippi, Emmanuelle; Delaunay, Régis; Rialan, Antoine; Rouault, Gilles; Druelles, Philippe; Castellant, Philippe; Coudert, Isabelle; Boulanger, Bertrand; et al.
Abstract: Background: Acute heart failure (AHF) complicating ST-segment elevation myocardial infarction (STEMI) is recognized as an ominous complication. Previous studies mostly reported outcomes of heterogeneous, non-contemporary population. Moreover, few studies assessed the prognosis of AHF according to its timing. This study evaluated incidence, predictors and impact of AHF according to its timing in a homogeneous STEMI patients population treated by primary percutaneous coronary intervention (pPCI). Methods: Data from 6282 patients included in a prospective multicenter registry were analyzed. Patients with AHF (Killip class > I) were compared to patients without AHF and patients with admission AHF were compared to patients who developed in-hospital AHF. In-hospital mortality was the primary endpoint of the study. Propensity-score matching and multivariable regression were used to adjust for confounders. Results: A total of 1328 patients (21.1%) presented AHF: 739 on admission and 589 during hospitalization. AHF was associated with a markedly increased in-hospital mortality rate (19.9% vs. 0.8%, p < 0.001). There was a gradual excess risk with each Killip class and admission AHF patients displayed the highest crude mortality rate (24.1%). By multivariable analysis, AHF was the strongest independent predictor of in-hospital mortality (HR = 3.852 (2.303–6.442), p < 0.001) without evidence of any difference according to its timing (HR = 0.947 (0.638–1.372), p = 0.767). These results were consistent after extensive adjustment on baseline characteristics in the matched cohorts. Among other predictors, pPCI beyond guidelines-recommended delays and stent thrombosis were independently associated with AHF. Conclusion: AHF regardless of its timing remains a common and dreadful complication of STEMI in the contemporary era.